Analisis Penyerapan Tenaga Kerja di Provinsi Bali Tahun 1994-2023 - I Gusti Ayu Aimee Widhiyanti; Wahyu Widodo (Universitas Diponegoro, 2024)
Human resources are one of the main factors in economic growth. Human resources plays a significant role in providing labor to produce goods and services in an economy. However, a large number of labor force could cause problems. Massive increases in the labor force without sufficient labor absorption could lead to unemployment. Unemployment is a problem that is often faced by local governments, one of which is Bali Province. This research aims to analyze the influence of minimum wages, domestic investment, and foreign investment on labor absorption in Bali Province. The data used is secondary data from the Bali Province Central Statistics Agency for the period of 1994 – 2023. By using multiple linear regression with the Ordinary Least Squares method, this research proved that minimum wage and foreign investment have a positive and significant effect on labor absorption, while domestic investment has a positive but not significant effect on labor absorption in Bali Province.